Pseudoexfoliation in south India. Issue 11 (10th November 2003) - Arvind, H; Raju, P; Paul, P G; Baskaran, M; Ve Ramesh, S; George, R J; McCarty, C; Vijaya, L
Abstract : Aim: To study the profile of pseudoexfoliation in a population based study. Method: 2850 consecutive subjects aged 40 years or older from a population based survey in a rural area of southern India underwent complete ophthalmic evaluation including history, visual acuity testing, refraction, slit lamp examination, applanation tonometry, gonioscopy, and dilated examination of the lens (including LOCS II grading of cataract), fundus, and optic disc. Patients with pseudoexfoliation syndrome were identified and their data were analysed with respect to age, sex, intraocular pressure, gonioscopic grading, cataract, and optic neuropathy. Results: 108 subjects had pseudoexfoliation syndrome (3.8 %). There was a significant increase in prevalence with age but no sex predilection. The condition was unilateral in 53 cases (49.1%) and bilateral in 55 cases (50.9%). 18 cases with pseudoexfoliation (16.7%) had high intraocular pressure (>21 mm Hg), 16 cases (14.8%) had occludable angles, and 14 cases (13%) had pseudoexfoliation glaucoma. There was a significantly higher prevalence of cataract among people with pseudoexfoliation compared to those without pseudoexfoliation (p = 0.014). Conclusion: The prevalence of pseudoexfoliation syndrome in the rural population of south India was 3.8%. Raised intraocular pressure was seen in 16.7% of people with pseudoexfoliation and glaucoma was present in 13%.